2013
DOI: 10.1177/0148607113482331
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Energy Expenditure and Oxygen Consumption

Abstract: There is circadian rhythm variation of energy expenditure and oxygen consumption with continuous and intermittent infusion for EN. This suggests that only one indirect daily calorimetric measurement is not able to show the patient's true needs. Energy expenditure is higher at night with both food administration methods. Moreover, energy expenditure and oxygen consumption are higher with the intermittent administration method at all times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Nevertheless, in the morning, DIT was slightly higher, energy balance (the difference 294 between energy intake and expenditure) lower, and early post-meal values of RQs and CHO oxidation 295 significantly increased, in line with our results [9]. Another study found a higher energy expenditure at night 296 during enteral nutrition, but it involved older patients hospitalized in a Neurologic unit on artificial nutrition, 297 therefore these results are difficult to be compared with those in our healthy individuals [11]. Sato found no 298 differences in 24-h energy expenditure in a room-size respiratory chamber between normal (7:00 pm) or late 299 (10:30 pm) evening meals in 10 young Japanese, but the measure of DIT was not available, the times of the two 300 experimental meals were not so different (approximately 3-h), and, consistent with our results, postprandial 301…”
Section: Energy Expenditure and Metabolic Responses To Mealssupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, in the morning, DIT was slightly higher, energy balance (the difference 294 between energy intake and expenditure) lower, and early post-meal values of RQs and CHO oxidation 295 significantly increased, in line with our results [9]. Another study found a higher energy expenditure at night 296 during enteral nutrition, but it involved older patients hospitalized in a Neurologic unit on artificial nutrition, 297 therefore these results are difficult to be compared with those in our healthy individuals [11]. Sato found no 298 differences in 24-h energy expenditure in a room-size respiratory chamber between normal (7:00 pm) or late 299 (10:30 pm) evening meals in 10 young Japanese, but the measure of DIT was not available, the times of the two 300 experimental meals were not so different (approximately 3-h), and, consistent with our results, postprandial 301…”
Section: Energy Expenditure and Metabolic Responses To Mealssupporting
confidence: 76%
“…It is 285 difficult to establish with our data if the higher increase in FFA AUC after the evening meal was the 286 consequence of insulin resistance or rather the cause of the impaired insulin sensitivity, because of the known 287 effects of FFA on the reduction in glucose uptake and phosphorylation in skeletal muscles and on the 288 impairment in insulin signaling and action [34][35]. 289 290 Not all the authors found a lower DIT after the evening meal [9][10][11][12]. Westrate failed to find a significant 291 difference between morning and afternoon DIT in 10 normal weight young men, but the fasting period was 292 shorter in the afternoon than in the morning and the metabolic conditions of the participants to this study 293…”
Section: Energy Expenditure and Metabolic Responses To Mealsmentioning
confidence: 80%
“…The glycogen metabolism of the liver is also linked to circadian oscillations with changes in glycogen synthase and storage, glycogen phosphorylase and glucose-6-phosphatase [53]. When 34 bedridden patients fed through nasoenteric tube had calorimetric energy expenditure measurements, it appeared that the values obtained were higher with the intermittend viz continuous infusion [54].…”
Section: Background Studiesmentioning
confidence: 99%